INOVASI PENDIDIKAN UNTUK MENINGKATKAN KESADARAN LINGKUNGAN SISWA SD DALAM KEGIATAN JAMBORE DI DESA MALASARI - Purwati, Dewi; Fadilah, Hafid; Maulana, Taupik; Fajar, Muhamad Andika; Hermala, Adinda; Sari, Rosa Fiolita; Yustian, Naurah Rabbani; Fitriyani, Sagita; Lisan, Asep Maulana Faisal; Fadilah, Muhamad Reza; Humairoh, Aninda Nishfi; Saputra, Aryo; Ramadhan, Ardika Rifky; Apriansyah; Al-Rasyid, Harun (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
This study aims to examine the effectiveness of educational innovation in enhancing elementary school students’ environmental awareness through jamboree activities in Malasari Village. The subjects of this research were elementary school students participating in the jamboree, with a focus on implementing experiential learning strategies in outdoor settings. To measure students’ metacognitive awareness regarding environmental issues, the Metacognitive Awareness Inventory was used and adapted to the context of environmental education. The findings reveal that educational innovation through jamboree activities improved students’ understanding of the importance of environmental conservation, fostered caring attitudes, and encouraged active participation in environmentally friendly practices. This study highlights that experiential, outdoor-based education can be an effective strategy for instilling environmental awareness and values from an early age.